1999
DOI: 10.1002/(sici)1097-0177(199908)215:4<352::aid-aja7>3.0.co;2-j
|View full text |Cite
|
Sign up to set email alerts
|

Zebrafishstat3 is expressed in restricted tissues during embryogenesis andstat1 rescues cytokine signaling in aSTAT1-deficient human cell line

Abstract: Transcription factors of the STAT family are required for cellular responses to multiple signaling molecules. After ligand binding‐induced activation of cognate receptors, STAT proteins are phosphorylated, hetero‐ or homodimerize, and translocate to the nucleus. Subsequent STAT binding to specific DNA elements in the promoters of signal‐responsive genes alters the transcriptional activity of these loci. STAT function has been implicated in the transduction of signals for growth, reproduction, viral defense, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0
1

Year Published

2000
2000
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 107 publications
(11 citation statements)
references
References 111 publications
(152 reference statements)
0
10
0
1
Order By: Relevance
“…Previous expression data, along with data presented here has revealed that piscine STAT1 is widely expressed in many tissues [30,31,46-49]. However, data concerning functional activity in lower vertebrates, such as STAT1 phosporylation and cellular localization upon stimulation of cells, is scarce.…”
Section: Discussionmentioning
confidence: 78%
“…Previous expression data, along with data presented here has revealed that piscine STAT1 is widely expressed in many tissues [30,31,46-49]. However, data concerning functional activity in lower vertebrates, such as STAT1 phosporylation and cellular localization upon stimulation of cells, is scarce.…”
Section: Discussionmentioning
confidence: 78%
“…Although the ERV-9 LTRs are found only in primates (1,4,6), we assumed that the LTR enhancer would function in Tg zebrafish, because transcription factors that may bind to the GATA, CCAAT, and CACCC motifs and activate the LTR enhancer are expressed in similar temporal fashion in zebrafish as in man and mouse (18)(19)(20). Breeding of the Tg zebrafish lines showed that in the Tg embryos, GFP expression was maternally inherited.…”
mentioning
confidence: 99%
“…LIF activation through the JAK1/STAT3 pathway has been shown to induce SOCS4 expression during ovarian follicular development [ 9 ], consistent with the strong levels of maternally derived socs4a transcripts observed. Moreover, the expression of zebrafish stat3 overlaps strongly with that of socs4a during embryogenesis, including in a variety of sensory neural structures, such as the ALLG, PLLG, TG and SAG [ 40 , 41 ]. Interestingly, zebrafish stat3 has been implicated in convergence/extension [ 40 ], with stat3 mutants displaying reduced A-P extension [ 42 ], as observed in socs4a morphants.…”
Section: Discussionmentioning
confidence: 99%